ANO-Rectal Primary Malignant Melanoma; CT Versus MR Imaging Features - Krishna Kumar Munivenkatappa; Sakthivel R; Anand Kumar B; Dharan Venkatesh KA (Asian Journal of Medical Radiological Research, 2022)
Anorectal malignant melanoma (AMM) is a rare and highly aggressive malignancy, shares similar appearance and clinical symptoms with low rectal cancer, presenting as an intraluminal polypoid mass accompanying a series of clinical symptoms, such as rectal bleeding, tenesmus and a change in bowel habits. In clinical practice, Computed tomography (CT) & magnetic resonance imaging (MRI) are the most commonly used modalities for evaluating and diagnosing anorectal lesions. The overlap in clinical symptoms and imaging findings make it easy to misdiagnose anorectal malignant melanoma as low rectal cancer, the most common malignancy in the anorectum. Currently, endoscopic biopsy is the routine procedure for pre-operative diagnosis of anorectal malignant melanoma. We present the clinical, CT and typical MR features seen in a 53-year-old woman diagnosed with melanoma of the anorectum.